A Review of Some Security Aspects of WiMAX and Converged Network - Habib, Masood; Ahmad, Masood (2010 Second International Conference on Communication Software and Networks, 2010)
The future for WiMAX-based mobile wireless access is so bright. With the increasing popularity of WiMAX, it is gaining a great position in the next generation of wireless networks. Due to the evolution of new technologies wireless is not secured as like others networking technologies. On the other side the trend is towards converged network in which the same networking infrastructure is used for both data and voice transmission. A lot of security concerns are needed to secure a converged network. This paper aims to review the study of WiMAX and converged network and security considerations for both the technologies. WiMAX security in converged network is studied. The security threats that can occur in converged network to WiMAX and countermeasures that can be taken against these threats are reviewed.